Activism for intersectional justice in sport sociology: Using intersectionality in research and in the classroom - Calow, Emma (Frontiers in Sports and Active Living, 2022)
This perspective paper considers what scholars and teachers of sport sociology can (un)learn by applying the concept of intersectionality in research and in the classroom. I focus on contemporary forms of activism in the context of sport in the United States (U.S.) and demonstrate intersectionality's utility through three examples of athlete activism from the past 10 years led by sports people. Although each example is focused on a particular axis of difference and domination, such as sexual harassment (read: gender) and Black Lives Matter (read: race), I show that the cause at stake is always already intersectional. This has consequences for the field of sport studies/sport sociology; in engaging in intersectional research, sport sociologists and researchers alike can inform policymakers in sport in the decision-making process. In the final part of the paper, I offer insight from my positionality as a graduate student through reflection on how I—and my colleagues—might understand our role within the “matrix of domination” that characterizes both our subject and our field. As novice sport scholars, graduate students can translate the theoretical meanings and purpose of intersectionality into lived reality by being intentional in what and how we teach and research. In this case, I suggest that intersectional justice in sport does not just mean on the track/field/court; it can also mean in the classroom, thereby expanding our notion of what activism “in sport” is and looks like.